VD_FINDINFO Décision / 2016 / 175 vom 10. März 2016 - VD Tribunal cantonal (2016)
DÉTENTION PROVISOIRE, RISQUE DE RÉCIDIVE, ACTE D'ORDRE SEXUEL AVEC UN ENFANT | 221 al. 1 let. c CPP (CH), 393 al. 1 let. c CPP (CH)